Pelaksanaan Pekerja Alih Daya Oleh Perusahaan Alih Daya Yang Tidak Terdaftar Pada Dinas Ketenagakerjaan Berdasarkan UU Ketenagakerjaan - Holyness N Singadimedja; Agus Pratiwi; Christine Nauli Pakpahan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Every entrepreneur competes to get maximum profit or profit oriented by reducing minimum expenses. One of the strategies undertaken is to cooperate with employers where a company can take workers who will work outside the production fields or the main fields of the outsourcing company. However, the implementation of outsourcing in recent years has still experienced problems due to the lack of regulations issued by the government as a form of anticipation of inequality in the implementation of work relations between employers and workers. This raises the potential for maladministration of the company due to the lack of strict supervision from Labor Inspectors. This study aims to identify the effectiveness of the Oversight function of the Department of Manpower for outsourced companies that do not register their companies with the local Office of Manpower and Transmigration. The research method used is a normative juridical method with research specifications that are descriptive analytical in nature of the applicable laws and regulations and legal theories associated with the actual practice of the implementation of labor inspection. The results of the study state that labor inspection is still not running optimally because the number of labor inspectors is not comparable to the objects of labor inspection.